Whistle-Blowing Policy as a Governance Tool: An Empirical Study of Earnings Management in Indonesian Companies - Hapsari, Dian Indriana; Welly, Yerisma; Sianipar, Martin Yehezkiel (Universitas Gorontalo, 2025)
This study aims to examine whether the implementation of Whistle-Blowing Policy (WHBLP) strengthens the effectiveness of Corporate Governance (CG) mechanisms in limiting earnings management (EM) practices in Indonesian manufacturing companies. The research adopts an empirical quantitative approach, using secondary data from manufacturing firms listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023. The sample was selected through purposive sampling, and data analysis was conducted using panel data regression and the Modified Jones Model (MJM) to measure discretionary accruals as a proxy for earnings management. The findings reveal that firms with well-structured internal controls and WHBLP can enhance monitoring mechanisms of CG, thus mitigating earnings management. However, the results also indicate that CG mechanisms are sometimes more effective in firms without WHBLP, suggesting the need for stronger policy enforcement. These findings provide practical implications for investors, shareholders, and policymakers in developing more effective whistle-blowing systems to improve corporate governance practices.